Ketertarikan Masyarakat Terhadap Kereta Cepat Jakarta – Bandung - Hanny Aqilah; Miftahul Hayati Rahmi Putri ; Silvina Dara Zelita (JOURNAL OF ADMINISTRATIVE AND SOCIAL SCIENCE, 2024)
Cooperation between Indonesia and China in building high-speed trains began with President Joko Widodo's visit to Beijing, China in November 2014. President Joko Widodo is interested in China's high-speed trains. The construction of the Jakarta-Bandung Fast Train is a collaborative effort with an agreement not to use funds from the State Revenue and Expenditure Budget (APBN). Indonesia has a requirement to do business only on a business-to-business (B2B) basis. The Jakarta-Bandung Fast Train is known to the public as an express train that meets people's needs and is highly praised for its service, comfort and supporting facilities. The construction of the Jakarta-Bandung express train is a government initiative to modernize transportation within the city, and has a significant impact on economic development and community mobility. This is considered very effective in overcoming traffic jams and minimizing losses for the government.